2016
DOI: 10.1002/rcm.7490
|View full text |Cite
|
Sign up to set email alerts
|

A simple heated‐capillary modification improves the analysis of non‐covalent complexes by Z‐spray electrospray ionization

Abstract: Rationale The observation of intact non-covalent complexes by ESI-MS hinges on the ability to minimize in-source activation processes that take place during analyte desolvation. We explored the merits of replacing the sampling cone of a standard Z-spray source with a heated capillary that makes the desolvation process slower and more gradual. We employed well-characterized protein-RNA and DNA-DNA assemblies to compare the alternative configurations. Methods Mass analysis evaluated the complexes’ integrity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…Again, the Orbitrap and FT-ICR possess heated transfer capillaries which transport the ions from atmosphere to partial vacuum. A heated transfer capillary modification to a Q-ToF platform 31 may prove beneficial for native Nd analysis. Conversely, the operating pressures and therefore the mean-free-path at which the MSP1D1-Nd (and bacteriorhodopsin) activation and subsequent desolvation (and protein liberation, in the case of bacteriorhodopsin) occurs are also very different and must be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Again, the Orbitrap and FT-ICR possess heated transfer capillaries which transport the ions from atmosphere to partial vacuum. A heated transfer capillary modification to a Q-ToF platform 31 may prove beneficial for native Nd analysis. Conversely, the operating pressures and therefore the mean-free-path at which the MSP1D1-Nd (and bacteriorhodopsin) activation and subsequent desolvation (and protein liberation, in the case of bacteriorhodopsin) occurs are also very different and must be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, experiments with the Z‐spray ionization source show no enhanced protonation regardless of the parameters employed. In addition, Fabris and coworkers have reported that the Z‐spray source can produce unwanted in‐source dissociation of noncovalent complexes (ie, some ions have sufficient energy to dissociate) . Therefore, the Z‐spray ionization process may destabilize the peptide‐Cr(III)‐water complex before an “extra” proton is transferred to peptide ions.…”
Section: Resultsmentioning
confidence: 99%
“…The Water ligands have an unusually long lifetime around Cr(III) due to a kinetic inertness to displacement. [11][12][13] The residence time of a water molecule in the first hydration shell 74 77 Therefore, the Z-spray ionization process may destabilize the peptide-Cr(III)-water complex before an "extra" proton is transferred to peptide ions. The absence of enhanced protonation in the Z-spray source further supports our hypothesis that this is a gas-phase or desolvation-phase effect, as opposed to a solution-phase effect occurring before the ESI event.…”
Section: Time Effectmentioning
confidence: 99%
“…A stainless‐steel wire was inserted into the emitter back end to provide typical spray voltages in the 0.9 to 1.2‐kV range. Source temperature and desolvation voltages were finely adjusted by monitoring the incidence of ammonium adducts and water clusters . The ion mobility experiments were completed in the 25‐cm TW cell by using a 90 mL/min flow of N 2 and 180 mL/min of He to maintain a constant pressure of ~4.40 mbar (uncalibrated gauge reading).…”
Section: Methodsmentioning
confidence: 99%
“…Source temperature and desolvation voltages were finely adjusted by monitoring the incidence of ammonium adducts and water clusters. 42 The ion mobility experiments were completed in the…”
Section: Mass Spectrometrymentioning
confidence: 99%